Advances in Negotiation Theory: Bargaining, Coalitions and Fairness - Carlo Carraro; Carmen Marchiori; Alessandra Sgobbi (Fondazione Eni Enrico Mattei (FEEM), 2005)
Bargaining is ubiquitous in real-life. It is a major dimension of political and business activities. It appears at the international level, when governments negotiate on matters ranging from economic issues (such as the removal of trade barriers), to global security (such as fighting against terrorism) to environmental and related issues (e.g. climate change control). What factors determine the outcome of negotiations such as those mentioned above? What strategies can help reach an agreement? How should the parties involved divide the gains from cooperation? With whom will one make alliances? This paper addresses these questions by focusing on a non-cooperative approach to negotiations, which is particularly relevant for the study of international negotiations. By reviewing non-cooperative bargaining theory, non-cooperative coalition theory, and the theory of fair division, this paper will try to identify the connection among these different facets of the same problem in an attempt to facilitate the progress towards a unified framework.
Keywords: C72; C78; 330; Negotiation theory; Bargaining; Coalitions; Fairness; Agreements